Is the Middle Meningeal Artery the Optimal Path for Dural Arteriovenous Fistula Embolization? - Su, Han; Xu, Kan; Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2021)
Background: The middle meningeal artery (MMA) is the optimal arterial path for endovascular treatment (EVT) of dural arteriovenous fistulas (DAVFs). However, the details are not completely understood. Materials and Methods: We performed a retrospective study of patients who were admitted to the First Hospital of Jilin University with a diagnosis of cranial DAVF with involvement of the MMA as a feeding artery. On the basis of the arterial path chosen and the role of the MMA in the first EVT procedure, EVT was divided into three types (I–III), each of which was further divided into two subclasses (a and b). The degree of embolization was analyzed. Result: The 104 included patients ranged in age from 13 to 80 years (mean, 53.6 ± 11.8 years). There were 48 cases of hemorrhage (46.2%, 48/104). Complete embolization was achieved in the first procedure in 64.4% of cases, and success was eventually achieved using EVT (the first attempt or a subsequent attempt) in 74.1% of cases. EVT caused complications in 6.7% of cases. A modified Rankin scale score of 0 or 1 was achieved in 78.8% of patients. Statistical analyses revealed that type Ia and IIb EVTs had the lowest complete embolization rates, but no difference was found between type Ia and IIb EVTs. Types IIa and III EVT had the highest complete embolization rates. Most cases had a good prognosis. Conclusion: These findings elucidate the features of the different EVT classes defined by the first EVT procedure and the role of the MMA. The delivery of treatment via slim and tortuous MMA branches increased the failure rate of EVT. A thick, straight MMA branch is the optimal path for treatment.